8 Developing a casemix classification for specialist palliative care: a multi-centre cohort study to develop a patient-specific prediction model for the cost of specialist palliative care using classification and regression tree analysis. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Murtagh, Fliss EM; Firth, Alice; Guo, Ping; Yip, Ka Man; Ramsenthaler, Christina; Douiri, Abdel; Pinto, Cathryn; Pask, Sophie; Dzingina, Mendwas; Davies, Joanna M; O'Brien, Suzanne; Edwards, Beth; et al.
Abstract : Background: There is wide inequity in specialist palliative care provision across settings. The absence of any standard way to group by case complexity is a barrier to addressing these inequities. Aim: We therefore aimed to develop a casemix classification for UK specialist palliative care across settings, by identifying/grouping patient-level attributes at the start of an episode of care that predict costs of care provision within that episode. Design: Cohort study with prospective collection of patient demographic and clinical variables, potential complexity and casemix criteria, and patient-level resource use. Results: 2, 469 participants were recruited (mean age 71.6, 51% male, 75% with cancer), receiving 2, 968 episodes of care, from 14 specialist palliative organisations across England. Episodes of care lasted: median (range) 8 days (1–402) in hospital advisory palliative care, 12 days (1–140) in inpatient palliative units, 30 days (1–313) in community palliative care. Median cost per day (interquartile range) were: £56 (£31–100) in hospital advisory, £365 (£176-£698) within inpatient, and £21 (£6-£49) in community care. Seven hospital advisory, six inpatient, six community casemix classes for specialist palliative care, based on seven casemix variables (pain, other physical symptoms, psychological symptoms, functional status, palliative Phase of Illness, living alone, and family distress) predict per-diem costs. Conclusion: The casemix classes show cost weight variations by up to 60% (in hospital advisory palliative care), up to 4.5-fold (in inpatient hospices), and approaching 3-fold (in community palliative care). The proposed casemix classification helps to understand these variations systematically and at scale; for practice, policy (including funding), and research, to help address inequities and provide fair, equitable and transparent palliative care to all who need it. Acknowledgements: Funded by National Institute for Health Research (C-CHANGE project: RP-PG-1210-12015). The views and opinions expressed by authors do not necessarily reflect those of the NHS, NIHR, MRC, CCF, NETSCC, or DHSC